Effectiveness of a mindfulness Intervention program on different indicators of stress and anxiety in primary school students aged 9 to 12 years. - Perez Segoviano, Luz Elvira; Aguilar-Zavala, Herlindaq; Hidalgo, Vanesa; Villada, Carolina (Anales de Psicología / Annals of Psychology, 2025)
Introduction: Late childhood or preadolescence is an important period of development in which high levels of anxiety and stress can occur due to physical and psychological changes; the efficacy of interventions such as mindfulness in reducing stress and anxiety at these ages has been under-examined. This study aimed to evaluate the effectiveness of a mindfulness intervention program on different indicators of stress and anxiety in primary school students aged 9 to 12 years belonging to a public primary school. Method: 125 children were evaluated in anxiety (STAIC), Stress (IIEC), emotional valence, arousal, perceived self-control (SAM), and salivary cortisol, before, during, and after the intervention (14 sessions in 5 weeks, three sessions a week, 40 minutes/session). Sixty-three children participated in an intervention group, and sixty-two children were enrolled in the control group (waist list). Results: After the intervention, a noteworthy decrease in the levels of perceived stress at school, arousal, and cortisol in saliva was observed. Conclusions: Mindfulness appears to be an appropriate tool for reducing perceived stress, particularly in the school setting, as it reduces perceived arousal and lowers cortisol levels after one month of intervention.